Rural NEETs: Individual features, challenges, and opportunities - Simões, F. (2024)
In this chapter, I present and discuss the main individual features of rural young people Not in Employment, nor in Education and Training (NEET) living in rural areas. These characteristics fit in the so-called individual system of the bioecological model. I start out by depicting rural NEETs educational background and gender differences within this subset of NEETs, due to their importance in shaping these young people’s pathways. Afterward, I elaborate on what is known to date about rural NEETs psychological profile, particularly regarding their cognitive skills, soft skills, and well-being. Finally, I will explore how these personal characteristics of rural NEETs may interact with emerging challenges and opportunities in rural communities located at other layers of the bioecological model. This chapter strongly relies on several contributions from the COST Action Rural NEET Youth Network, as well as on the most relevant international scholarship and policy reports focusing on rural communities’ development, youth employment, and school-to-work transition, to achieve an interdisciplinary understanding of rural NEETs individual traits and features.